1963
DOI: 10.1128/jb.86.4.702-707.1963
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Bacteriocines of Enterococci

Abstract: has been made of bacteriocine production by a wide variety of well-characterized strains of group D streptococci. On the basis of spectrums and sensitivity to chloroform, heat, and proteolytic enzymes, five distinct bacteriocines can be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(49 citation statements)
references
References 8 publications
3
46
0
Order By: Relevance
“…Of the 19 indicators 18 were enterocinogenic, so that enterocine production and sensitivity co-exist in these organisms: 5 of the 19 strains were sensitive to their own enterocine. Similar results were not reported by Kjems (1955), but Brock et al (1963) consider that a strain is always resistant to its own enterocine. Fredericq (1956) takes the same view with regard to colicines and colicinogenic strains, but Ryan, Fried & Mukai (1955) found one strain sensitive to its own colicine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of the 19 indicators 18 were enterocinogenic, so that enterocine production and sensitivity co-exist in these organisms: 5 of the 19 strains were sensitive to their own enterocine. Similar results were not reported by Kjems (1955), but Brock et al (1963) consider that a strain is always resistant to its own enterocine. Fredericq (1956) takes the same view with regard to colicines and colicinogenic strains, but Ryan, Fried & Mukai (1955) found one strain sensitive to its own colicine.…”
Section: Discussionsupporting
confidence: 90%
“…Although Pohonek (1961) postulated that bacteriocine-producing enterococci may be able to replace vaginal lactobacilli sensitive to these products, the role of enterocines in the ecology of the organisms remains uncertain. The fact that > 50% of the strains examined by Brock, Peacher & Pierson (1963) produced enterocines leads to the supposition that thcy must play some roIe in the life of bacteria. I n the present work an attempt has been made to determine the frequency of enterocinogeny and lysogeny in enterococci, and the sensitivity of the strains examined to their own inhibitory substances.…”
mentioning
confidence: 99%
“…Among the studies on bacteriocins produced by Enterococcus spp. (Brock et al 1963;Brandis 1979;Lopez-Lara et al 1991) there are only few reports demonstrating inhibitory activity against L. monocytogenes (Kramer and Brandis 1975;McKay 1990) and only recently, Arihara et al (1991) reported the inhibition of L. monocytogenes by three strains of Ent. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…This clas sification may not be complete because of the limited number of test strains. Brock et al [5] similarly described five types of bac teriocins produced by hemolytic and nonhemolytic enterococci. Pleceas, et al [12] presented 25 types of group D streptococci by sensitivities against 12 strains of entero cine producer.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of bacteriocin production was closely related to the presence in the cell of a stable genetic factor composed of deoxyribonucleic acid (DNA) [9,14]. Bacteriocin in group D streptococci was described by Kjem [10] and Brock et al [5]. Brock and Davie [4] stated that both hemolysin and bacteriocin produced by Streptococcus faecalis var.…”
mentioning
confidence: 99%